ANALISIS RETORIKA FERRY IRWANDI DALAM VIDEO YOUTUBE: “HOW TO BE A GOOD STORYTELLER” - Indah Sulmayanti; Mimin Trianjani; Listia Eka Sari; Uswatun Hasanah (PENTAS : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2025)
The development of digital media has changed the pattern of public communication, including in delivering persuasive messages. This study aims to analyze the rhetorical strategies used by Ferry Irwandi in a YouTube video entitled How To Be a Good Storyteller. This study uses a qualitative descriptive method through observation and content analysis techniques. The focus of the study refers to three elements of classical rhetoric: speaker credibility (ethos), emotional appeal (pathos), and logical reasoning (logos). The results of the study show that Ferry Irwandi consistently integrates these three elements in delivering his narrative. He builds ethos through personal experience, activates pathos with a relaxed and familiar language style, and composes logos sequentially and systematically. This study concludes that classical rhetorical strategies remain relevant and effective in increasing the persuasive power of communication in the digital era.